FENOMENA KIAI DALAM DINAMIKA POLITIK: Antara Gerakan Moral dan Politik - Abdurrahman, Abdurrahman (STAIN PAMEKASAN, 2012)
Abstrac A kiai (muslim cholar) leadership must be intensively observed, since it describes the patron of its connection with the community. The power of kiais leadership has been centralistic in nature. The authority and the power of kiai in society include both social and political relationship. In terms of factual-empirical phenomena, this assumption matches the facts that show that all the political parties competing in general election use kiai to be vote getters. It influences politic attitude of loyal grass roots. However, in certain situation, the influence of kiai becomes meaningless due to the diverged authority of kiai. Kata-kata kunci Kiai, politik, citra, moral